2017
DOI: 10.3892/ol.2017.6279
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanism of GA-13315 on the proliferation and apoptosis of KB cells in oral cancer

Abstract: The present study describes the effects and mechanism of GA-13315 on the proliferation and apoptosis of KB cells in oral cancer. Oral cancer is twice as common in men than women. More than 90% of oral cancers in men and 85% in women are linked to lifestyle and environmental factors. PPP2R2B methylation may be associated with survival and prognosis in patients with gliomas. In tumor cell proliferation and apoptosis, the mechanism of PPP2R2B remains unclear. In the present study, we found that PPP2R2B expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…cell proliferation, with or without Ga-13315 treatment, was measured using a cell Counting Kit-8 (CCK-8) assay kit (BD Biosciences). Briefly, cells were seeded into 96-well plates at 2,000 cells/plate, incubated overnight and treated with various doses (4,8,16 and 32 ng/µl) of Ga-13315 or the vehicle control for 48 h. Then, 10 µl ccK8 solution was added to each well and cells were incubated for an additional 2.5 h. optical density was measured by a microplate reader (Thermo Fisher Scientific, inc.) at a wavelength of 450 nm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…cell proliferation, with or without Ga-13315 treatment, was measured using a cell Counting Kit-8 (CCK-8) assay kit (BD Biosciences). Briefly, cells were seeded into 96-well plates at 2,000 cells/plate, incubated overnight and treated with various doses (4,8,16 and 32 ng/µl) of Ga-13315 or the vehicle control for 48 h. Then, 10 µl ccK8 solution was added to each well and cells were incubated for an additional 2.5 h. optical density was measured by a microplate reader (Thermo Fisher Scientific, inc.) at a wavelength of 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…in GA-13315-treated lung cancer cells cassette subfamily B member 1 (7). it inhibited proliferation and caused apoptosis in oral cancer (8). The product of the protein phosphatase 2 regulatory subunit Bbeta (PPP2r2B) gene belongs to the phosphatase ii regulation subunit B family, which serves important roles in cell growth and division (9).…”
Section: Trim67 Promotes Nf-κb Pathway and Cell Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated the inhibitory effect of GA-13315 on proliferation of A549 cells in xenograft mice models [12]. In addition, more recent evidence revealed that GA-13315 inhibited the growth and proliferation of oral, breast, and leukemia tumor cells through exerting antiangiogenic activity [12, 14], and the value of inhibitory concentration 50 (IC 50 ) in various tumor cell lines ranged from 0.13 to 30.28 μg/ml. However, the antitumor effect and the underlying mechanism of GA-13315 on human lung adenocarcinoma have not been fully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits the growth and also accelerates the apoptosis of KB oral cancer cells. GA-13315 also possesses anti-angiogenic properties [77,78].…”
mentioning
confidence: 99%